2009
DOI: 10.1073/pnas.0900226106
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania amazonensispromastigotes induce and are killed by neutrophil extracellular traps

Abstract: Neutrophils are short-lived leukocytes that die by apoptosis, necrosis, and NETosis. Upon death by NETosis, neutrophils release fibrous traps of DNA, histones, and granule proteins named neutrophil extracellular traps (NETs), which can kill bacteria and fungi. Inoculation of the protozoan Leishmania into the mammalian skin causes local inflammation with neutrophil recruitment. Here, we investigated the release of NETs by human neutrophils upon their interaction with Leishmania parasites and NETs' ability to ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
467
4
18

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(511 citation statements)
references
References 31 publications
22
467
4
18
Order By: Relevance
“…In Lb infection, patients displaying lymphadenopathy without ulceration exhibited a higher proportion of neutrophils and eosinophils in lymph node aspirates (35). It is possible that neutrophils are able to directly kill Lb promastigotes in vivo through, for example, the formation of neutrophil extracellular traps, as recently documented with L. amazonensis (36). Nonetheless, the macrophage is considered a major effector cell of the immune response during cutaneous leishmaniasis since it is able to produce inflammatory cytokines that are ultimately responsible for parasite killing and elimination.…”
Section: Discussionmentioning
confidence: 90%
“…In Lb infection, patients displaying lymphadenopathy without ulceration exhibited a higher proportion of neutrophils and eosinophils in lymph node aspirates (35). It is possible that neutrophils are able to directly kill Lb promastigotes in vivo through, for example, the formation of neutrophil extracellular traps, as recently documented with L. amazonensis (36). Nonetheless, the macrophage is considered a major effector cell of the immune response during cutaneous leishmaniasis since it is able to produce inflammatory cytokines that are ultimately responsible for parasite killing and elimination.…”
Section: Discussionmentioning
confidence: 90%
“…Leishmania promastigotes, the infectious form transmitted through the insect vector, are trapped in NETs, resulting in rapid killing [32]. Immunoneutralization of histones can abrogate killing of the parasites, supporting the antiparasitic activity of histones.…”
Section: Antiparasitic Activitymentioning
confidence: 99%
“…The results showed that NETs are formed during the early stages of infection. In addition to the reported induction of NETosis formation by bacteria [3,6,12,13], fungi [17][18][19] and protozoa [15], NETosis has also been shown to be induced by LPS-activated platelets [14] and by antineutrophil autoantibodies isolated from patients with SVV [16], whereas impaired degradation of NETs has been associated with systemic lupus erythematosus as well [20].…”
Section: Introductionmentioning
confidence: 98%
“…Data collected over the past 5 years demonstrate the in vivo occurrence of NETosis in different clinical settings such as appendicitis [3], necrotizing fasciitis [12], pneumonia [13], sepsis [14], leishmaniasis [15] and small vessel vasculitis (SVV) [16], suggesting a pathophysiological relevance in these conditions. Recently, the kinetics of in vivo NET formation in murine lungs in response to Aspergillus infection was monitored [17].…”
Section: Introductionmentioning
confidence: 99%